1999
DOI: 10.1002/jlb.66.6.953
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a CSF-induced proliferating subpopulation of human peripheral blood monocytes by surface marker expression and cytokine production

Abstract: The phenotype of a subpopulation(s) of human monocytes which has been shown to proliferate in vitro in response to macrophage colonystimulating factor (M-CSF or CSF-1) and granulocyte-macrophage CSF (GM-CSF) is as yet unknown. To identify this proliferating subpopulation(s) we demonstrated first that DNA synthesis was occurring under culture conditions suitable for flow cytometric evaluation. Flow cytometric analysis of surface antigen expression identified that after 5 days of culture the proliferating subpop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 53 publications
3
31
0
Order By: Relevance
“…3]). These results were similar for several donors and in agreement with recent findings suggesting that a small subset of human blood monocytes may be osteoclast precursors with proliferative properties (14,24,55). In addition, we confirmed that immature (day 4) and LPSmatured MDDCs (day 8) resided in the G 0 phase of the cell cycle (Fig.…”
Section: Genetic Modification Of Immature Mddcs Is Greatly Enhanced Usupporting
confidence: 93%
“…3]). These results were similar for several donors and in agreement with recent findings suggesting that a small subset of human blood monocytes may be osteoclast precursors with proliferative properties (14,24,55). In addition, we confirmed that immature (day 4) and LPSmatured MDDCs (day 8) resided in the G 0 phase of the cell cycle (Fig.…”
Section: Genetic Modification Of Immature Mddcs Is Greatly Enhanced Usupporting
confidence: 93%
“…Of the 52 genes that are overexpressed in RA PBMCs, 21 (40%) were in this 'monocyte-enriched' group. Thus, the presence of these genes may reflect in part the increased numbers 7,8 or activation of monocytes in RA PBMCs compared with controls (see below).…”
Section: Resultsmentioning
confidence: 99%
“…Brefeldin A (10 g/ml; Sigma-Aldrich) was added to the cultures for the final 2 h of LPS stimulation to limit cytokine secretion (29). Following FcR blocking, cells were stained for CD11b (Mac-1 ␣-chain; M1/70-allophycocyanin) as above, fixed in 4% paraformaldehyde, and permeabilized using 0.5% saponin and 2% FCS in PBS.…”
Section: Intracellular Cytokine Stainingmentioning
confidence: 99%